Modelo comunitario de reducción de riesgos para el manejo de agua de consumo humano de la comunidad de Gradas parroquia Veintimilla canton Guaranda - Mullo Agualongo, Neptali Eliezer (2021)
The present research work called "Community Risk Reduction Model for the management of water for human consumption in the community of Gradas parroquia Veintimilla cantón Guaranda" aims to evaluate the risks (natural and anthropogenic) of water for human consumption to establish measures risk reduction. To determine the risk level of the catchment, conduction and storage system, it was based on the PMI methodology in the PMBOK guide fifth edition, modified, strengthening with field work, interview with the board of directors of the Water Administration Board, it is worth mentioning that The present study is descriptive-explanatory because the identification and evaluation of natural and anthropic phenomena is carried out. The factors that influence the deterioration of hydrographic sources were identified, taking as natural risks (landslide, earthquake, volcanic eruption and rock falls) and anthropogenic (water pollution and forest fires). Each of the variables were assigned a value of indicators and weighting, the sum, multiplication and division and comparison gives us the result of each variable.